Evaluasi Penyelenggaraan Tiket Terpadu Antar Moda (TITAM) di Stasiun Gambir - Maimunah, Siti (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2011)
Organizing TIT AM or inter-modal integrated ticketing is a form of public transport service impravement in praviding service and convenience for the users in order to support the implementation of inter-modal transport effectively and efficiently. By using conjoint analysis method is expected to knaw the preferences of respondents in the implementation of TIT AM, while the descriptive analysis is used to evaluate the implementation TIT AM. The results shaw that not many people who knaw TITAM evident from the survey results there are 60% of respondents do not know TITAM. Hawever, the expected of respondents by TITAM implementation is to increase comfort and to reduce queues in the purchase of tickets to make shorter travel time. Through conjoint analysis method was concluded that the willingness of society to the implementation of TIT AM are buying tickets online and manual (in combination), and type of electronic tickets, as well as connecting mode of train, bus and ship the first choice of respondents who indicated the highest utility or satisfaction for service users. Keywords: integrated ticket, conjoint analysis